The development of LaptopSeeker mobile system with Global Positioning System (GPS) / Mohd Hafizz Hishamuddin - Hishamuddin, Mohd Hafizz (2017)
The project aim is to develop LaptopSeeker, a mobile application that focus on problems that faced by buyer and seller of laptop. Buying a laptop is not an easy task when buyers have little knowledge about laptop or have no experience buying any laptop before. The buyers who have little knowledge and no experience might purchase unsuitable laptop for their desired specification which may lead to frustration. Apart from that, the project also focuses on perspective of seller. The project enables the sellers to easily promote their product through the system which can help sellers to expand their business and attract more customers. LaptopSeeker is equipped with Global Positioning System (GPS) feature. The GPS in the system is beneficial to the user to allocate the supplier for their desired laptop. Besides, GPS is a mechanism that is commonly used in the real world nowadays for user to find what they want. Furthermore, the project is developed using Mobile Application Development Life Cycle(MADLC) methodology because it is common methodology for Android mobile application and aligned with the flow of project objectives. MADLC methodology is adapted to four phases like identification, design, development and prototyping phase. Each phase consist of several activities that carried out to achieve the project objective through step by step. In conclusion, the mobile application developed can help buyer to find the suitable laptop and assist seller in promoting their product.